Penerapan Diskresi Penuntutan Berdasarkan Keadilan Restoratif Terhadap Tindak Pidana Bernilai Kerugian Ekonomis Rendah - Pradana, Rido; Danil, Elwi; Elda, Edita (Faculty of Law, Andalas University, 2025)
This research explains the comparison of prosecutorial discretionary in Indonesia with other countries, indicators of determining low economic loss crimes based on laws and regulations and the application of prosecutorial discretionary to low economic loss crimes in cases in the jurisdiction of the West Sumatra High Prosecutor's Office. This research uses a normative legal research method with a statutory approach, a case approach and a comparative approach based on secondary data through literature studies. The results of this research indicate that prosecutorial discretionary in Indonesia and other countries is basically the authority of the public prosecutor in carrying out their duties in the field of prosecution to prosecute or not to prosecute a case, but each country has certain criteria in applying prosecutorial discretionary to a crime. In the provisions of laws and regulations, there are no clear indicators regarding low economic loss crimes because there is no classification of criminal acts based on economic losses, so that each law enforcement officer has its own discretion in determining indicators of low economic loss crimes. The indicator of low economic loss crimes is currently still influenced by the indicator of criminal fines. Prosecutorial discretionary for low economic loss crimes can be resolved by using a restorative justice approach that can accommodate the economic loss value of a crime. In this research, the author suggests that indicators be regulated clearly and firmly to determine the minimum and maximum limits of the nominal value of low economic loss crimes for law enforcement officers for the sake of legal certainty in law enforcement.